Effect of Obesity on Left Ventricular Longitudinal Myocardial Strain by Speckle Tracking Echocardiography in Children and Adolescents - Kibar, Ayşe Esin (Balkan Med J, 2015)
BACKGROUND: Impaired subclinical ventricular function may contribute to the risk of cardiovascular disease in obesity. AIMS: The aim of this study was to determine the influence of obesity on left ventricular (LV) longitudinal myocardial function in normotensive obese children using two-dimensional (2D) speckle tracking echocardiography (STE). STUDY DESIGN: Case-control study. METHODS: Sixty normotensive obese children aged 10–16 years (mean age, 13.9±2.3 years) were compared with 50 normal-weight controls. Obese participants had a body mass index (BMI)≥95(th) percentile. Regional strain/strain rate (SR) values were compared with left ventricular (LV) parameters. The correlation was studied by linear regression analysis. RESULTS: Obese subjects exhibited a significantly higher LV end-diastolic diameter, left atrium/aortic diameter ratio, and LV mass/index when compared to controls (p<0.001). Left ventricular ejection fraction and regional systolic myocardial velocities were similar in the obese and control groups. By 2D STE, regional strain of both the septal wall (average strain: −16.0±3.9% vs −21.9±2.4%, p<0.001) and lateral wall (average strain: −15.6±2.3% vs −22.9±3.5%, p<0.001); regional SR of both the septal wall (average SRsys: −0.7±0.22 s(−1) vs −1.3±0.32 s(−1), p<0.001) and lateral wall (average SRsys: −0.67±0.19 s(−1) vs −1.33±0.31 s(−1), p<0.001); regional SR(E/A) of both the septal wall (average SR(E/A): 1.8±0.83 vs. 2.2±0.91, p: 0.004) and lateral wall (average SR(E/A): 1.4±0.43 vs. 2.4±1.21, p<0.001); and global strain (−14.6±7.34% vs −20.9±3.24%, p<0.001) were lower in the obese group compared with the controls. These strain imaging parameters appear to be related to the severity of obesity and can contribute to increased BMI. Left ventricular mass was found to be correlated with a decrease in global LV strain. CONCLUSION: Our study showed that childhood obesity is associated with an alteration in the longitudinal LV function. Segmental analysis of the LV can provide subtle markers for the emergence of future obesity-related cardiac disease.